Baicalein protects isoproterenol induced myocardial ischemic injury in male Wistar rats by mitigating oxidative stress and inflammation - Kumar M.; Kasala E.R.; Bodduluru L.N.; Dahiya V.; Lahkar M. (My University, 2025)
Objective: The aim of the present study was to investigate the cardioprotective effects of baicalein, main bioactive constituent from roots of Scutellaria baicalensis and Scutellaria lateriflora, on isoproterenol (ISO) induced acute myocardial infarction model in rats and to explore the underlying mechanisms. Method: Rats were treated with baicalein (50 mg/kg and 100 mg/kg) orally for 14 days and on 13th and 14th day, myocardial injury was induced by ISO injection (100 mg/kg, subcutaneous) at an interval of 24 h. Result: Our study showed that ISO administration resulted in significant elevations in the levels of cardiac injury biomarkers such as cardiac troponin I, creatine kinase-MB, AST and ALT. Concentrations of reactive nitrogen species and reactive oxygen species in the heart tissue increased significantly while antioxidant enzymes level declined. The levels of tissue pro-inflammatory cytokines tumor necrosis factor-α and interleukin-6 were significantly increased after ISO administration. Pretreatment with baicalein significantly reversed these alterations induced by ISO administration. Exploration of the underlying mechanisms of protective effect of baicalein pretreatment revealed that it repressed the expression of nuclear factor kappa B and restored the ISO induced elevation of pro-inflammatory cytokines, oxidative and nitrosative stress. We found that baicalein pretreatment enhanced the level of antioxidant defense enzymes like SOD, catalase and GSH. Furthermore, the present study also demonstrated cardioprotective effects of baicalein by the histopathological findings. Conclusion: Taken together, our findings demonstrated that baicalein pretreatment might have a potential benefit in prevention and terminating ischemic heart diseases like myocardial infarction. © 2016, Springer International Publishing.